A novel fault detection technique for PV systems based on the K-means algorithm, coded wireless Orthogonal Frequency Division Multiplexing and thermal image processing techniques. (1st May 2022) - Et-taleby, Abdelilah; Chaibi, Yassine; Boussetta, Mohammed; Allouhi, Amine; Benslimane, Mohamed
Highlights: A PV fault detection technique based on the K-means algorithm, coded wireless OFDM and thermal image processing is proposed. The k-means, Min-sum algorithms, and OFDM modulation offer an excellent detection of faults in PV panels in real-time. The Min-sum algorithm offers significant performance to detect and correct errors induced by a noisy wireless channel. This solution is cost-effective with an overall capital cost around 5.41 USD/m 2. Abstract: Solar energy is considered one of the most ecological energy systems, which provides clean, reliable, and unlimited power. However, the solar system can be exposed during its operation to numerous failures that can immediately lead to a dangerous incident such as fire ignition. To ensure the productivity and safety of the system, it must be accompanied by fault detection and diagnostic (FDD) techniques. A new wireless communication system and its application in PV systems to detect damaged areas of solar panels are proposed to address these issues. The proposed approach is composed mainly of two parts; the first part aims to check and detect the existence of damaged areas in the thermal images of PV panels, while the second part focuses on the transmission of faulty panels using Orthogonal Frequency Division Multiplexing (OFDM) modulation with three decoding algorithms, namely, Min-sum, Bit-Flipping, and Viterbi, to send and correct errors induced by a wireless transmission channel. The simulation results have shown that employing the K-means algorithm, OFDM modulation, and the Min-sum decoding scheme offers a significant performance improvement giving a rapid degradation with a BER of 10 −4 for SNR = 3.7 dB and a null BER from SNR = 4 dB. From a financial point of view, it was proved that the adopted solution is cost-effective compared to literature-based ones. This solution could be very useful since the overall capital cost is about 5.41 USD/m 2 .